Initial Experience With the Outback Catheter for Targeted Reentry During Subintimal Angioplasty of the Infragenicular Arteries. (April 2018) - Diamantopoulos, Athanasios; Santonocito, Serafino; Thulasidasan, Narayanan; Gkoutzios, Panos; Ahmed, Irfan; Zayed, Hany; Katsanos, Konstantinos
Purpose: To report use of the Outback reentry device for targeted distal reentry during subintimal recanalization of chronic total occlusions (CTOs) in the infragenicular arteries.Methods: During an 18-month period, the Outback device was applied in 10 patients (mean age 71.8±18.8 years; 8 men) to achieve reentry at the infragenicular segment following either unsuccessful spontaneous reentry after subintimal crossing of a CTO or when a targeted reentry was desired. The mean occlusion length was 117.5±101.0 mm. Technical (device) success, overall procedure success, and reentry accuracy are reported, along with any major or minor complications.Results: The device was technically successful in achieving reentry in 9 of 10 cases; overall procedure success was achieved in 8 owing to heavy calcifications in a distal posterior tibial artery and a distal popliteal artery. The reentry accuracy was 10.8±14.6 mm. There were no major complications and only 3 minor sequelae, including 2 dissections and 1 small perforation; all were treated successfully with stenting.Conclusion: The Outback device has a high technical success rate in achieving targeted true lumen reentry in infragenicular subintimal angioplasty when spontaneous reentry is not possible or a targeted reentry is desirable.